STATE SPONSORED TERRORISM AS A TOOL FOR PROXY WAR - Lee, Brice Tseen Fu; Sims, Juan Pablo; Kornphetcharat, Kotchaphop (Journal of Terrorism Studies, 2025)
This paper explores the role of state-sponsored terrorism as a tool in proxy wars, examining its effectiveness in achieving short-term geopolitical objectives and its long-term consequences. By analyzing historical and contemporary case studies, such as Iran’s support for Hezbollah and Pakistan’s backing of militant groups in Kashmir, the paper demonstrates how states use financial, military, and intelligence resources to empower non-state actors. The analysis applies realist, constructivist, and asymmetrical warfare theories to understand the motivations behind state sponsorship and the risks involved, including blowback and international sanctions. The paper concludes by assessing the future of state-sponsored terrorism in light of evolving global security dynamics and counter-terrorism measures.